Decorative laminated film for solar cell module
By using a decorative laminated film with an optimized layer on the solar cell module, the problem that the decorative layer in the prior art is difficult to take into account both designability and high light transmittance, and efficient decoration of the solar cell module is achieved.
Patent Information
- Application Number
- CN202380052924.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-23
- Filing Date
- 2023-08-23
- Publication Date
- 2025-03-04
AI Technical Summary
The decorative layers of existing solar cell modules are difficult to take into account both design and high light transmission, resulting in a decrease in the power generation efficiency of solar cells.
Decorative laminated film for solar cell modules with protective film, hard coating, decorative layer, support layer and adhesive layer are used to ensure that the total light transmittance and reflectivity are within a specified range by optimizing the refractive index of the adhesive layer and the luminous pigment orientation of the decorative layer.
The high light transmittance and design of the solar cell module are achieved, and the adverse effects on power generation efficiency are avoided, and the decorative layer can be easily peeled off and replaced.
Smart Images

Figure CN119563392A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a decorative laminate film for a solar cell module. Background Art
[0002] In recent years, attempts have been made to install solar cells on the walls of buildings to generate solar power. However, conventional solar cell modules are visible from the outside, which makes them lack design quality. If they are installed on the outer wall of a building, this is required to be improved.
[0003] However, if Figure 1 As shown, it is known that if the light transmittance of the film provided on the solar cell is reduced, the output of the solar cell is reduced. That is, the layer with design usually absorbs and reflects visible light. Therefore, if a decorative layer is provided, the transmittance of light is reduced, thereby reducing the power generation efficiency of the solar cell. Therefore, a decorative laminated film is required that can impart design without reducing the energy efficiency of the solar cell. The output required for a solar cell module varies depending on the use and purpose. For example, in addition to solar cell modules that emphasize artistic output and are almost zero when provided in museums and art galleries, in order to achieve ZEH (zero energy home) and ZEB (zero energy building), it is actually necessary to ensure an output of more than 60% compared to the case of no decoration.
[0004] Patent document 1 discloses a coating for forming a lower layer and a surface-coated solar cell having a laminate on the surface, wherein the coating for forming the lower layer contains specific components and is cured by irradiation with active energy rays, and is used to form a lower layer that becomes a base of a hard coating layer, and the laminate is composed of a lower layer obtained by using the coating for forming the lower layer and a hard coating layer. However, such a laminate is for the purpose of improving weather resistance and does not show high light transmittance. Furthermore, since no pigment is mixed, it is not considered to give design properties.
[0005] Patent Document 2 discloses a decorative laminate film for a solar cell module that contains an effect pigment and has little loss in solar cell efficiency.
[0006] Patent Documents 3 and 4 disclose a decorative layer including a bright pigment and having a light transmittance of 50% or more, and a solar cell module including the decorative layer.
[0007] These decorative laminated films have high light transmittance and can therefore suppress reduction in output of solar cells and also impart design properties. However, development of a decorative laminated film that can impart more distinctive design properties is desired.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2013-119553
[0011] Patent Document 2: International Publication No. 2019 / 1220793
[0012] Patent Document 3: Japanese Patent Application Publication No. 2021-027364
[0013] Patent Document 4: Japanese Patent Application Publication No. 2021-027266 Summary of the invention
[0014] Problems to be solved by the invention
[0015] In view of the above circumstances, an object of the present invention is to provide a decorative film for a solar cell module which has excellent design and high light transmittance and also has excellent performance such as weather resistance and moisture and heat resistance for protecting a solar cell module.
[0016] Means for solving problems
[0017] The present invention relates to a decorative laminate film for a solar cell module, which is a decorative laminate film for a solar cell module having a protective film (A), a hard coating layer (B), a decorative layer (C), a support layer (G) and an adhesive layer (F), characterized in that:
[0018] The decorative laminate film (L) in a state where the protective film (A) is peeled off from the decorative laminate film for a solar cell module has a total light transmittance Tt of 50% to 90% at a wavelength of 380nm to 810nm, and a reflectance R of 5% to 40% at a wavelength of 380nm to 1300nm.
[0019] The adhesive layer has a refractive index Fa of 1.3 or more and 1.8 or less.
[0020] The adhesive strength between the decorative laminate film (L) and the solar cell module in a state where the protective film (A) is peeled off from the decorative laminate film for a solar cell module is preferably 1 N / 25 mm or more and 50 N / 25 mm or less.
[0021] The difference |Fa-Fg| between the refractive index Fa of the adhesive layer and the refractive index Fg of the surface of the solar cell module is preferably 0 or more and 0.5 or less.
[0022] The decorative laminate film for a solar cell module is preferably removable after being bonded to the solar cell module.
[0023] The hard coat layer is preferably a layer formed from a thermosetting coating composition or an active energy ray-curable coating composition.
[0024] The decorative laminate film for a solar cell module preferably has a surface roughness Ra(C) of the decorative laminate film (L) from which the protective film is peeled off at a rate of 5.0 mm / sec and a surface roughness Ra(P) of the side from which the protective film is peeled off that satisfies the following formula (1).
[0025] 50.0≤[Ra(C) / Ra(P)]×100≤ 210.0 (1)
[0026] The decorative laminate film for a solar cell module preferably has a surface free energy γac of the decorative laminate film (L) in a state where the protective film is peeled off and a surface free energy γap on the peeled side of the protective film satisfying the following formula (2).
[0027] 50.0≤(γac / γap)×100≤110.0 (2)
[0028] In the decorative laminate film for a solar cell module, it is preferred that the Martens hardness HM(L) of the decorative laminate film (L) in a state where the protective film is peeled off satisfies the following formula (3).
[0029] 2.0N / mm 2 ≤HM(L)≤50.0N / mm 2 (3)
[0030] Effects of the Invention
[0031] The decorative film for solar cell module of the present invention has excellent design and high light transmittance. Therefore, it is possible to decorate the solar cell without causing adverse effects on the power generation efficiency of the solar cell. In addition, since it is adhered to the substrate through the adhesive layer, it can be easily peeled off when replacing the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a graph showing the relationship between the total light transmittance and the output of a solar cell.
[0033] Figure 2 This is a diagram showing the layer structure of the decorative film for a solar cell module in the present invention.
[0034] Figure 3 This is a diagram showing the layer structure of the decorative film for a solar cell module in the present invention.
[0035] Figure 4 This is a diagram showing the layer structure of the decorative film for a solar cell module in the present invention.
[0036] Figure 5 This is a diagram showing the layer structure of the decorative film for a solar cell module in the present invention. DETAILED DESCRIPTION
[0037] The present invention is described in detail below.
[0038] The decorative laminate film for solar cell modules of the present invention is a decorative laminate film for solar cell modules comprising a protective film (A), a hard coating layer (B), a decorative layer (C), a supporting layer (G) and an adhesive layer (F), and is characterized in that the total light transmittance Tt at a wavelength of 380nm to 810nm of the decorative laminate film (L) in a state where the protective film (A) is peeled off from the decorative laminate film for solar cell modules is 50% to 90%, the reflectivity R at a wavelength of 380nm to 1300nm is 5% to 40%, the refractive index Fa of the adhesive layer is 1.3 to 1.8, and the bonding strength between the decorative laminate film (L) in a state where the protective film (A) is peeled off from the decorative laminate film for solar cell modules and the solar cell module is 1N / 25mm to 50N / 25mm.
[0039] One of the characteristics of the solar cell module decorative laminate film of the present invention is that it can be bonded to a substrate via an adhesive layer. In the conventional solar cell module decoration, the mainstream is to directly form a coating film on glass or to firmly bond it to a substrate via an adhesive.
[0040] When decorating by such a method, the function of the decorative layer decreases due to aging, and the appearance deteriorates. When it is necessary to peel off the decorative layer and form a new decorative layer, the old decorative layer is not easy to peel off. The present invention has the advantage of being able to easily peel off in such a case.
[0041] The decorative laminate film for a solar cell module of the present invention has a refractive index Fa of the adhesive layer of 1.3 to 1.8. In addition, the difference |Fa-Fg| between the refractive index Fa of the adhesive layer and the refractive index Fg of the surface of the solar cell module is preferably set to 0 to 0.5.
[0042] For conventional decorative laminated films, due to the difference in refractive index of the multiple layers, total reflection occurs when light is incident at a shallow angle, and the amount of light entering the interior decreases, which hinders the effective use of light and may not achieve the desired power generation efficiency. This problem can be improved by making the difference in the refractive index of the adhesive layer within the above range. That is, if the reflectivity is reduced, the amount of sunlight reaching the solar cell module increases, thereby maintaining the output of the solar cell, which is preferred from this point of view.
[0043] The decorative laminated film for solar cell module of the present invention also has a support layer. By having a support layer, the strength of the laminated film can be maintained, and the weather resistance and construction workability can be improved. In addition, since the strength is maintained, it also has the advantage of being able to be peeled off without breaking after being attached to the solar cell module. That is, the laminated film deteriorated over time can also be peeled off and a new laminated film can be attached.
[0044] In addition, the total light transmittance Tt of the solar cell module decorative laminate film of the present invention at a wavelength of 380nm to 810nm is 50% or more and 90% or less when the protective film is peeled off. By ensuring the light transmittance, it is possible to have a more excellent power generation efficiency and design. In order to ensure such high light transmittance, it is preferred to mix a bright pigment in the decorative layer and improve the orientation of the bright pigment in the decorative layer.
[0045] As the bright pigment, a flat plate-like pigment is generally used. Such a bright pigment is highly oriented in a direction parallel to the film surface in the film layer, so that diffuse reflection of light is controlled and high light transmittance can be maintained.
[0046] Furthermore, if a bright pigment having light interference properties is used as the bright pigment, design properties can be obtained by the light interference effect, and design properties can be obtained without impairing light transmittance.
[0047] In order to make such a decorative layer have high light transmittance, it is preferred that the bright pigment present in the decorative layer is highly aligned parallel to the surface direction of the coating film. To obtain such a high degree of orientation, it is preferred to use a method other than film formation based on conventional general coating.
[0048] A specific method for forming such a decorative layer will be described later.
[0049] In addition, the reflectivity R of the decorative laminated film for solar cell modules of the present invention at a wavelength of 380nm to 1300nm is 5% to 40% in a state where the protective film is peeled off. The above-mentioned reflectivity R refers to the ratio of the reflected light beam from the laminated film to the sunlight incident on the surface of the laminated film, calculated by the spectral reflectivity obtained in a specified wavelength region. If the above-mentioned reflectivity is within the above-mentioned range, the reflected light of the light incident on the laminated film is easily perceived by the human eye. That is, the color and pattern of the laminated film are visually recognized, and on the other hand, it is difficult to visually recognize the solar cell unit. Therefore, it is inferred that a solar cell module with excellent design can be obtained.
[0050] The reflectance R is preferably 15% or more and 30% or less.
[0051] In the present invention, the total light transmittance Tt and reflectance R of the decorative laminate film for a solar cell module refer to the values obtained by measuring the total light transmittance and reflectance of the decorative laminate film (L) with the protective film peeled off.
[0052] In the present invention, the total light transmittance is a value measured by using a spectrophotometer U-4100 (Hitachi High-Technologies) in a wavelength range of 380.0 nm to 810.0 nm using an integrating sphere. A halogen lamp was used as a light source during the measurement.
[0053] In the present invention, the above-mentioned reflectivity can be calculated as follows: For the prepared laminated film, a U-3310 spectrophotometer (manufactured by Hitachi) is used to measure the ratio of the intensity of the light irradiated from the light source and the intensity of the light reflected from the laminated film in the range of 380nm to 1300nm in wavelength scanning mode at a scanning speed of 300nm / min and a sampling interval of 0.5nm, thereby calculating the reflectivity.
[0054] Hereinafter, the decorative laminate film for solar cells of the present invention will be described in detail.
[0055] (Layer composition)
[0056] The decorative laminate film for solar cell module of the present invention comprises a protective film (A), a hard coating layer (B), a decorative layer (C), a support layer (G) and an adhesive layer (F). These layers are preferably formed in the order of protective film (A), hard coating layer (B), decorative layer (C), support layer (G) and adhesive layer (F) (see Figure 2 ). A layer is formed by bonding the film having such a structure to a solar cell as a substrate. Then, the protective film (A) can be peeled off.
[0057] In addition, the decorative laminated film for solar cell modules of the present invention may have other layers such as a bonding layer and a printed layer as required. By having a printed layer, a good design layer can be formed by printing, which is preferred from this aspect. In the case of having a printed layer, the decorative layer (C) can be replaced by a printed layer. In addition, the printed layer may also be located between the support layer (G) and the adhesive layer (F) (see Figure 4 ).
[0058] When a printed layer is provided between the adhesive layer (F) and the support layer, a transparent filler layer (H) may be provided to fill the height difference of the printed layer (see Figure 5 ).
[0059] Hereinafter, each layer constituting the solar cell decorative laminate film of the present invention will be described in detail.
[0060] (Decorative layer (C))
[0061] The decorative laminated film for a solar cell module of the present invention comprises a decorative layer (C).
[0062] For the decorative layer (C), when decorating a solar cell module, the properties such as designability, light transmittance, weather resistance, and moisture and heat resistance are required. From the perspective of imparting these properties, a layer formed by a thermosetting coating composition is preferably used. The thermosetting coating composition comprises a main agent and a curing agent, wherein the main agent preferably comprises particles of a polyol and a bright pigment, and the curing agent preferably comprises an isocyanurate compound. The bright pigment is not particularly limited, and examples thereof include metal particles such as aluminum, chromium, gold, silver, copper, brass, titanium, nickel, nickel-chromium, and stainless steel, mica, metal oxides, pearlescent pigments, glass flakes coated with metals or metal oxides, silica flakes coated with metal oxides, graphite, hologram pigments, and cholesteric liquid crystal polymers.
[0063] In addition, as the above-mentioned bright pigment, commercial products such as Iriodin (registered trademark), Pyrisma (registered trademark), Xirallic (registered trademark), Miraval (registered trademark), Colorstream (registered trademark), RonaStar (registered trademark), Biflair (registered trademark), and Lumina Royal (registered trademark) can also be used. In addition, other commercial products such as Colorstream (registered trademark), Xirallic (registered trademark), Miraval (registered trademark), and Ronastar (registered trademark) can also be used.
[0064] As the bright pigment, these may be used alone or in combination of two or more.
[0065] The bright pigment is preferably a flaky bright pigment. More specifically, the size in the plane direction is preferably 1 μm to 300 μm and the thickness is preferably 0.1 μm to 10 μm. By allowing such a flat bright pigment to exist in the coating film in a highly oriented state, the design properties can be appropriately exerted.
[0066] The size and thickness of the flaky bright pigment in the plane direction are measured by electron microscope observation to calculate the surface area. The thickness is a value measured by a method of calculating the thickness from specific gravity, weight, and surface area. It should be noted that the size in the plane direction refers to the major diameter, which represents the average value of the major diameter measured for 100 particles randomly selected from the particles appearing in the image of the electron microscope photograph.
[0067] The above-mentioned bright pigment is preferably interference aluminum oxide flakes, interference mica flakes, glass flakes, interference silicon dioxide flakes and / or interference talc flakes. These bright pigments are flaky bright pigments, and are preferred from the aspect of being able to obtain design properties through the interference of light. Among them, interference mica flakes and glass flakes are preferred.
[0068] The blending amount of the above-mentioned bright pigment is preferably 0.1% to 60% by mass relative to the total solid content of the decorative layer. By using the above-mentioned blending amount, a decorative layer (C) having both design and light transmittance can be formed, which is preferred from this aspect. The above-mentioned blending amount is more preferably 1% to 50% by mass, and further preferably 5% to 30% by mass.
[0069] The thickness of the decorative layer is not particularly limited, but is preferably 10 μm to 100 μm, more preferably 5 μm to 70 μm, and even more preferably 10 μm to 50 μm.
[0070] It should be noted that in the decorative laminate film for solar cell modules of the present invention, the amount of bright pigment blended in the decorative layer and the thickness of the decorative layer have a significant influence on the light transmittance. Therefore, it is important to adjust these and obtain a predetermined light transmittance.
[0071] The decorative layer (C) can be obtained, for example, by a two-component coating composition composed of a main agent and a curing agent. The curing component contained in the main agent is not particularly limited, and is preferably at least one polyol selected from the group consisting of acrylic polyols, polyester polyols, polyether polyols and polycarbonate polyols, and preferably at least one selected from the group consisting of acrylic polyols, polyester polyols and polyether polyols. In addition, the hydroxyl value of the polyol is preferably 50 mgKOH / g or more and 1000 mgKOH / g or less.
[0072] Examples of the curing agent include trimer isocyanurate compounds of hexamethylene diisocyanate.
[0073] The ratio of the isocyanate group equivalent of the isocyanurate compound to the hydroxyl group equivalent of the polyol: NCO / OH is preferably 0.5 / 1 or more and 2 / 1 or less.
[0074] As the resin of the decorative layer (C), a polyurethane resin can be used.
[0075] The polyurethane resin contained in the decorative layer (C) is not particularly limited, but the Mw of the polyurethane resin is preferably 10,000 to 200,000, more preferably 30,000 to 150,000. When the Mw is 10,000 or more, the flexibility of the design layer is improved, and when the Mw is 200,000 or less, the production of the coating material for the decorative layer (C) and the coating properties on the substrate film are improved.
[0076] The Tg of the polyurethane resin is preferably -30 to 30° C. If the Tg of the polyurethane resin is -30° C. or higher, the tackiness (blocking) of the coating film after application and drying is improved, while if it is 30° C. or lower, the coating film hardness is reduced, the moldability is improved, and the physical properties of the product at low temperatures are also improved.
[0077] The decorative layer may further contain other pigments other than bright pigments. By containing other pigments, the design can be further improved. It should be noted that when using other pigments other than bright pigments, the total light transmittance Tt of the decorative laminate film for solar cell modules is preferably 50% or more and 90% or less.
[0078] The above-mentioned other pigments may also be added to the main agent. Examples of the above-mentioned other pigments include coloring pigments and extender pigments.
[0079] Examples of the coloring pigments include organic coloring pigments such as azo chelate pigments, insoluble azo pigments, condensed azo pigments, diketopyrrolopyrrole pigments, benzimidazolone pigments, phthalocyanine pigments, indigo pigments, perindole pigments, perylene pigments, dioxane pigments, quinacridone pigments, isoindolinone pigments, and metal complex pigments; and inorganic coloring pigments such as chrome yellow, yellow iron oxide, red iron oxide, carbon black, and titanium dioxide. These may be used alone or in combination of two or more.
[0080] As the above-mentioned extender pigment, for example, calcium carbonate, barium sulfate, clay and talc can be mentioned. They can be used alone or in combination of two or more. The content of the coloring pigment and the extender pigment is not particularly limited and can be appropriately set according to the type of pigment, purpose, etc.
[0081] The decorative layer may further contain additives commonly used in the coating field and the coating field as other components. Specifically, solvents, surface conditioners, viscosity regulators, antioxidants, defoamers, catalyst aids, rust inhibitors, anti-settling agents, dispersants, etc. may be cited. These additives may be added to the main agent or to the curing agent. The amount of the additives is not particularly limited and may be appropriately set as needed.
[0082] In the present invention, the decorative layer is preferably formed by a method in which the coating composition is adjusted to have a viscosity within a range of 50 mPa·s to 5000 mPa·s at 25° C. and applied by applying a shear force.
[0083] By forming the decorative layer by such a method, a higher degree of orientation can be achieved compared to the case where the bright pigment is applied by a conventional coating method. Therefore, it is preferred from the viewpoint that the decorative layer (C) can contain the bright pigment in the range of 1 wt % to 40 wt % and the total light transmittance Tt of the decorative laminate film for solar cell modules can be maintained at 50% or more.
[0084] (Protective film (A))
[0085] The film forming the protective film (A) is not particularly limited, and examples thereof include biaxially stretched films such as biaxially stretched polyester films and biaxially stretched polypropylene films, soft vinyl chloride films, unstretched polypropylene films, unstretched polyester films, polycarbonate films, acrylic resin films, fluorine films and other conventionally known films. Among them, films formed of polyester and / or polyolefin are preferred, and in particular, biaxially stretched polyester films are more preferred in order to be applicable to flat substrates without requiring formability (stretchability) from the perspective of energy saving and low temperature processability, and unstretched polyester films are more preferred in order to be applicable to three-dimensional shapes and requiring formability (stretchability). The thickness of the protective film (A) is preferably 0.01 mm to 0.5 mm, and more preferably 0.02 mm to 0.3 mm.
[0086] As the protective film (A) of the present invention, a protective film having a concavo-convex shape on the surface can be used. If such a film is used, the concavo-convex shape of the protective film (A) is transferred to the hard coating layer (A), thereby, a design with a roughness based on the concavo-convex feeling can be obtained, which is preferred from this point of view. The concavo-convex shape here is not particularly limited, as long as it can be visually identified and the degree of roughness in the design can be obtained.
[0087] The decorative laminate film for a solar cell module preferably has a surface roughness Ra(C) of the decorative laminate film (L) from which the protective film is peeled off at a rate of 5.0 mm / sec and a surface roughness Ra(P) of the side from which the protective film is peeled off that satisfies the following formula (1).
[0088] 50.0≤[Ra(C) / Ra(P)]×100≤ 210.0 (1)
[0089] By satisfying the above formula (1), the concavo-convex shape of the protective film (A) can be appropriately transferred, and a desired coating film surface can be obtained.
[0090] The protective film may be coated with a release agent on one or both of the surfaces, for example, the surface on the hard coating layer side and the surface on the opposite side to the hard coating layer side.
[0091] (Hard coating (B))
[0092] The decorative laminated film for a solar cell module of the present invention comprises a hard coating layer (B).
[0093] The hard coat layer (B) used in the present invention is preferably formed from a thermosetting coating composition or an active energy ray-curable coating composition, and its specific composition is not particularly limited as long as the physical properties as a decorative laminate film are not impaired.
[0094] The hard coat layer (B) forms the outermost layer when decorating a solar cell module, and therefore requires properties such as weather resistance and moisture and heat resistance. Therefore, it is preferable to use a layer formed from a thermosetting coating composition or an active energy ray-curable coating composition having excellent properties.
[0095] The thermosetting coating composition and active energy ray-curable coating composition are not particularly limited, and conventionally known compositions can be used. In addition, they may be aqueous compositions or solvent-based compositions, and may be single-component or two-component.
[0096] As the above-mentioned thermosetting coating composition, for example, a two-liquid coating composition consisting of a main agent comprising a polyol and a curing agent comprising an isocyanurate compound can be cited. By mixing the main agent and the curing agent, the polyol and the isocyanurate compound react to obtain a cured coating film. The main agent and / or the curing agent can be heated and / or vacuum degassed before mixing, respectively. Thus, the amount of water contained in the two-liquid coating composition obtained by mixing the two decreases, and the appearance of the obtained coating film is easily improved.
[0097] (Main agent)
[0098] The main agent includes a polyol. The polyol is a coating film forming resin. The polyol reacts with a curing agent, for example, by heating to form a cured coating film. Hereinafter, the curable resin containing a polyol contained in the two-liquid coating composition is sometimes collectively referred to as a coating film forming resin. The main agent may include a curing catalyst.
[0099] Hereinafter, each component will be described in detail.
[0100] <Polyol>
[0101] Polyol is a coating film forming resin. Polyol reacts with a curing agent, for example, by heating to form a cured coating film. Polyol has two or more hydroxyl groups per molecule. Thus, the hardness of the resulting coating film tends to increase. Polyol can be used alone or in combination of two or more.
[0102] The main agent preferably comprises a polyol (A1) having three or more hydroxyl groups per molecule and a polyol (A2) having two hydroxyl groups per molecule. The ratio of the polyol (A1) to the polyol (A2) is not particularly limited. The ratio of the polyol (A2) may be less than 50% by mass of the total of the polyol (A1) and the polyol (A2), may be less than 40% by mass, or may be less than 30% by mass.
[0103] The hydroxyl value of the polyol is preferably 50 mgKOH / g or more and 1000 mgKOH / g or less. When the hydroxyl value of the polyol is within the above range, the reaction rate of the polyol and the isocyanate compound increases when the main agent and the curing agent are mixed.
[0104] When two or more polyols are included, the apparent hydroxyl value calculated based on the hydroxyl value and mass ratio of each polyol is 100 mgKOH / g or more and 1000 mgKOH / g or less. That is, the main agent may include a polyol having a hydroxyl value of less than 100 mgKOH / g and / or a polyol having a hydroxyl value of more than 1000 mgKOH / g.
[0105] The hydroxyl value of the polyol (including the apparent hydroxyl value, the same below) is more preferably 60 mgKOH / g or more, and further preferably 100 mgKOH / g or more. The hydroxyl value of the polyol is more preferably 800 mgKOH / g or less, and further preferably 700 mgKOH / g or less.
[0106] The type of polyol is not particularly limited. As the polyol, for example, polyester polyol, polyether polyol, polycarbonate polyol, polyacrylic acid polyol and polyol can be cited. They can be used alone or in combination of two or more. Among them, the polyol preferably includes at least one selected from the group consisting of polyester polyol, polyacrylic acid polyol and polycarbonate polyol.
[0107] The polyester polyol preferably has a branched structure. The polyester polyol having a branched structure can be prepared, for example, by reacting two or more polycarboxylic acids with a trivalent or higher polyol compound, and repeating the above reaction as necessary.
[0108] Examples of commercially available polyester polyols include Desmophen VPLS2249 / 1 (manufactured by Sumika Covestro Urethane Company, Ltd.), Desmophen 800 (manufactured by Sumika Covestro Urethane Company, Ltd.), Desmophen XP2488 (manufactured by Sumika Covestro Urethane Company, Ltd.), Kuraray Polyol P-510 (manufactured by Kuraray Co., Ltd.), and Kuraray Polyol F-510 (manufactured by Kuraray Co., Ltd.).
[0109] Polyacrylic acid polyol is obtained by copolymerizing a polymerizable acrylic acid monomer having one or more hydroxyl groups in one molecule with other monomers copolymerizable therewith. Examples of polymerizable acrylic acid monomers having one or more hydroxyl groups in one molecule include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxypentyl (meth)acrylate, (meth)acrylate monoester of glycerol, (meth)acrylate monoester of trimethylolpropane, and 2-hydroxy-3-chloropropyl (meth)acrylate, or ring-opening polymerization adducts of the above (meth)acrylates having active hydrogen and lactones such as ε-caprolactone and γ-valerolactone.
[0110] As other monomers copolymerizable with the polymerizable acrylic monomer having one or more hydroxyl groups in one molecule, for example, (meth)acrylic acid, or (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, decyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate, styrene, or styrene derivatives such as α-methylstyrene and β-chlorostyrene, vinyl esters such as vinyl acetate, vinyl propionate, and vinyl isopropionate, or nitriles such as (meth)acrylonitrile can be cited. In addition, polymerizable adducts obtained by addition reaction of acrylic acid or methacrylic acid with monoepoxy compounds or epoxy resins can also be used.
[0111] The hydroxyl value of the acrylic polyol is preferably 2 or more.
[0112] Polycarbonate polyols can be prepared, for example, by reacting dimethyl carbonate with a polyol.
[0113] Examples of commercially available products of polycarbonate polyol include DURANOL T5650E (manufactured by Asahi Kasei Corporation), C-590 (manufactured by Kuraray Co., Ltd.), and ETERNACOLL PH-50 (manufactured by Ube Industries, Ltd.).
[0114] Examples of the polyol include ethylene glycol, glycerin, trimethylolpropane, propylene glycol, tetramethylene glycol, and pentaerythritol.
[0115] The weight average molecular weight (Mw) of the polyol is not particularly limited and the Mw of the polyol may be appropriately set according to the hydroxyl value and the like.
[0116] The main agent may also contain other film-forming resins other than polyols. Examples of the film-forming resin include acrylic resins, polyester resins, alkyd resins, polyether resins, polyolefin resins, polyurethane resins, polycarbonate resins, melamine resins, epoxy resins, and carbodiimide resins. Other film-forming resins may be used alone or in combination of two or more.
[0117] <Curing Catalyst>
[0118] The main agent may contain a curing catalyst. The curing catalyst is a component that promotes the curing reaction. The curing catalyst is not particularly limited, and from the perspective of the promotion effect, it is preferably at least one of the organometallic catalysts containing a metal element selected from the group consisting of Bi, Zn, Al, Zr and Sn. Among them, it is preferably at least one of the organometallic catalysts containing a metal element selected from the group consisting of Bi, Zn, Al and Zr.
[0119] As an organic metal catalyst containing Bi, for example, bismuth carboxylic acid and its salts can be mentioned. As an organic metal catalyst containing Zn, for example, zinc complex catalysts can be mentioned. As an organic metal catalyst containing Al, for example, aluminum complex catalysts can be mentioned. As an organic metal catalyst containing Zr, for example, zirconium chelate catalysts can be mentioned. As an organic metal catalyst containing Sn, for example, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate and other dialkyltin dicarboxylates; tin oxide compounds such as dibutyltin oxide; tin carboxylates such as 2-ethylhexanoic acid tin.
[0120] (Curing agent)
[0121] The thermosetting coating composition contains a curing agent, which improves the corrosion resistance and durability of the resulting coating film through a cross-linking reaction with a polyol or the like.
[0122] The curing agent contains an isocyanurate compound. The isocyanurate compound is a trimer of an isocyanate compound and has a ring structure.
[0123] The isocyanate compound is not particularly limited, and substances known as curing agents for two-liquid reaction-type compositions can be used. Examples include aromatic diisocyanates such as toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), xylylene diisocyanate (XDI), and meta-xylylene diisocyanate (MXDI); aliphatic diisocyanates such as hexamethylene diisocyanate (HDI), tetramethylene diisocyanate, 2-methyl-pentane-1,5-diisocyanate, 3-methyl-pentane-1,5-diisocyanate, lysine diisocyanate, and triethylene diisocyanate; and alicyclic diisocyanates such as isophorone diisocyanate (IPDI), cyclohexyl diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, norbornane diisocyanate, hydrogenated toluene diisocyanate, hydrogenated xylene diisocyanate, and hydrogenated tetramethylxylene diisocyanate. These may be used alone or in combination of two or more.
[0124] Among them, aliphatic diisocyanates are preferred, and HDI is more preferred, because of their relatively low viscosity. The trimers of these isocyanates have particularly high reactivity with polyols.
[0125] The ratio of the isocyanate group equivalent of the isocyanate compound to the hydroxyl group equivalent of the polyol: NCO equivalent / OH equivalent is preferably 0.5 / 1 to 2 / 1, more preferably 0.9 / 1 to 1.2 / 1.
[0126] The curing agent may include other curing agents other than the isocyanurate compound. As other curing agents, for example, amino resins, monomers or dimers of the above-mentioned isocyanate compounds, biuret bodies of the above-mentioned isocyanate compounds, end-capped products of the above-mentioned isocyanate compounds, epoxy compounds, aziridine compounds, carbodiimide compounds, and oxazoline compounds may be cited. They may be used alone or in combination of two or more.
[0127] The content of the curing agent is, for example, 35% by mass or more and 90% by mass or less of the resin solid content of the coating composition. The above content of the curing agent is preferably 45% by mass or more, more preferably 55% by mass or more. The above content of the curing agent is preferably 85% by mass or less, more preferably 70% by mass or less.
[0128] (Solvent)
[0129] The content of the solvent is 30% by mass or less. According to this embodiment, even in such a composition with a small amount of solvent and high viscosity, the aggregation of the glittering particles can be suppressed. Therefore, a coating film with a glittering feeling can be formed by in-mold coating. The content of the solvent is preferably 20% by mass or less, more preferably 10% by mass or less, and may also be 0%.
[0130] The solvent is not particularly limited. The solvent is usually an organic solvent. Examples of organic solvents include ester solvents such as ethyl acetate, butyl acetate, isopropyl acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate; ether solvents such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, methyl methoxybutanol, ethoxypropanol, ethylene glycol isopropyl ether, ethylene glycol tert-butyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, methoxybutanol, and propylene glycol monobutyl ether; alcohol solvents such as methanol, ethanol, butanol, and propanol; ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as Swasol, Shellsol, and mineral spirits; aromatic solvents such as xylene, toluene, Solvesso-100 (S-100), and Solvesso-150 (S-150). They can be used alone or in combination of two or more.
[0131] (other)
[0132] The two-liquid coating composition may contain other ingredients as needed. As other ingredients, additives commonly used in the coating field and the coating field may be cited. Specifically, light stabilizers, ultraviolet absorbers, various pigments, surface regulators, viscosity regulators, antioxidants, ultraviolet light blocking agents, defoamers, catalyst aids, rust inhibitors, anti-settling agents, dispersants, etc. may be cited. These additives may be added to the main agent or to the curing agent. The amount of the additive is not particularly limited and may be appropriately set as needed.
[0133] The active energy ray-curable coating composition is a monomer, oligomer or polymer that can be crosslinked and cured by radiation. As the active energy ray-curable resin in the present invention, from the aspects of being able to increase the crosslinking density after curing, being able to increase the effect of improving the surface hardness, and being able to increase the effect of improving the transparency, it can include multifunctional (meth)acrylate compounds such as multifunctional (meth)acrylate monomers, multifunctional (meth)acrylate oligomers, or multifunctional (meth)acrylate polymers. It should be noted that "(meth)acrylate" here means acrylate and / or methacrylate. It should be noted that in this specification, multifunctional (meth)acrylate compounds refer to compounds that do not have a polyurethane structure, and do not include the following polyurethane acrylates. In addition to the above-mentioned multifunctional (meth)acrylate compounds, the active energy ray-curable resin may also include monofunctional (meth)acrylate compounds.
[0134] The active energy ray-curable resin that can be included in the active energy ray-curable coating composition may include, for example, urethane acrylate. In one embodiment, the active energy ray-curable coating composition includes a polyfunctional (meth)acrylate compound and urethane acrylate.
[0135] As the urethane acrylate, a urethane acrylate monomer, oligomer, polymer or a combination of at least two of them can be used. As an example, urethane acrylate, urethane methacrylate, aliphatic urethane acrylate, aliphatic urethane methacrylate, aromatic urethane acrylate, aromatic urethane methacrylate, etc. can be cited. Among them, a multifunctional urethane acrylate oligomer having a molecular weight of 1000 to 10000 can be preferably used.
[0136] The active energy ray-curable coating composition of the present invention may, for example, contain a multifunctional polyurethane acrylate having 2 or more acrylate groups and an ester skeleton. By containing the multifunctional polyurethane acrylate, the resulting coating layer can exhibit sufficient adhesion to the transparent polymer substrate. In addition, by making the refractive index of the formed hard coat layer within the above-specified range, interference fringes can be prevented. The number of acrylate groups is 2 or more, preferably 2 to 4. If it is a monofunctional polyurethane acrylate, the reactivity may be reduced, and the adhesion and hardness may be reduced depending on the molecular weight. If the number of functional groups is too large, the adhesion may be reduced due to curing shrinkage.
[0137] The polyfunctional (meth)acrylate (compound) is obtained, for example, by reacting a polycarbonate diol (a) (hereinafter sometimes referred to as component (a)), a (meth)acrylate compound (b) containing two hydroxyl groups and two ethylenically unsaturated groups in the molecule (hereinafter sometimes referred to as component (b)), and a polyisocyanate (c) (hereinafter sometimes referred to as component (c)).
[0138] The polycarbonate diol (a) may be a diol having a straight chain or branched chain and having 2 to 10 carbon atoms, represented by HO-(ROC(=O)-O)-R'OH (wherein R and R' are the same or different straight chain or branched alkylene groups having 2 to 10 carbon atoms, and the number of carbon atoms is the total number of R and R'). Specifically, R or R' in the above formula may include ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, cyclohexylene, neopentylene, nonylene, 2-methyl-1,8-octylene, etc., and two or more of these may be used in combination. Among these, polycarbonate diol synthesized from 1,5-pentanediol and / or 1,6-hexanediol is preferred. In addition, as component (a), one compound may be used alone, or two or more thereof may be used in combination. Examples include etc. These multifunctional acrylates may be used alone, or two or more thereof may be used in combination.
[0139] Specific examples of the (meth)acrylate compound (b) containing two hydroxyl groups and two ethylenically unsaturated groups in the molecule include (meth)acrylic acid adducts of propylene glycol diglycidyl ether, (meth)acrylic acid adducts of 1,6-hexanediol diglycidyl ether, (meth)acrylic acid adducts of ethylene glycol diglycidyl ether, (meth)acrylic acid adducts of 1,4-butanediol diglycidyl ether, (meth)acrylic acid adducts of 1,5-pentanediol diglycidyl ether, (meth)acrylic acid adducts of 1,7-heptanediol diglycidyl ether, (meth)acrylic acid adducts of 1,8-octanediol diglycidyl ether, etc. In addition to these, (meth)acrylic acid adducts of neopentyl glycol diglycidyl ether, (meth)acrylic acid adducts of bisphenol A diglycidyl ether, and (meth)acrylic acid adducts of hydrogenated bisphenol A diglycidyl ether may be mentioned. Among these, acrylic acid adducts of propylene glycol diglycidyl ether and acrylic acid adducts of 1,6-hexanediol diglycidyl ether are preferred.
[0140] There are no particular restrictions on the polyisocyanate (c), and for example, diisocyanate compounds such as aliphatic diisocyanate compounds, alicyclic diisocyanate compounds, and aromatic diisocyanate compounds can be preferably used. Specifically, toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate, xylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methylcyclohexane-2,4 (or 2,6)-diisocyanate, 1,3-(isocyanate methyl)cyclohexane, isophorone diisocyanate, trimethylhexamethylene diisocyanate, dimer acid diisocyanate, dianisidine diisocyanate, Acid esters, phenyl diisocyanate, halogenated phenyl diisocyanate, methylene diisocyanate, ethylene diisocyanate, butylene diisocyanate, propylene diisocyanate, octadecylene diisocyanate, 1,5-naphthalene diisocyanate, polymethylene polyphenylene diisocyanate, triphenylmethane triisocyanate, naphthalene diisocyanate, toluene diisocyanate polymer, diphenylmethane diisocyanate polymer, hexamethylene diisocyanate polymer, 3-phenyl-2-ethylene diisocyanate, isocyanate 2,4-Propylbenzene diisocyanate, 4-methoxy-1,3-phenylene diisocyanate, 4-ethoxy-1,3-phenylene diisocyanate, 2,4'-diisocyanate diphenyl ether, 5,6-dimethyl-1,3-phenylene diisocyanate, 4,4'-diisocyanate diphenyl ether, benzidine diisocyanate, 9,10-anthracene diisocyanate, 4,4'-diisocyanate benzyl ester, 3,3'-dimethyl-4,4'-diisocyanate diphenylmethane, 2,6-dimethyl -4,4'-diisocyanate diphenyl ester, 3,3'-dimethoxy-4,4'-diisocyanate diphenyl ester, 1,4-anthracene diisocyanate, phenylene diisocyanate, 2,4,6-toluene triisocyanate, 2,4,4'-triisocyanate diphenyl ether, 1,4-tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,10-decamethylene diisocyanate, 1,3-cyclohexylene diisocyanate, 4,4'-methylene-bis(cyclohexyl isocyanate), and the like.
[0141] As a production example of polyfunctional urethane acrylate, the above components (a) to (c) can be placed in an organic solvent (such as methyl ethyl ketone) and reacted at elevated temperature as required. The completion of the reaction can be confirmed by the absence of isocyanate groups by infrared absorption spectroscopy.
[0142] The multifunctional urethane acrylate preferably has a weight average molecular weight of 20,000 to 60,000, and more preferably has a weight average molecular weight of 30,000 to 50,000. Regarding the weight average molecular weight of the multifunctional urethane acrylate, if the molecular weight is too high, the viscosity increases, the smoothness is impaired, and the interference fringes deteriorate, and if the molecular weight is too low, the viscosity decreases, the smoothness of the coating surface cannot be maintained, and the interference fringes deteriorate.
[0143] In addition, from the aspect of adhesion, the multifunctional polyurethane acrylate preferably has a hydroxyl value of 0 to 20 mgKOH / g, and more preferably has a hydroxyl value of 0 to 5 mgKOH / g. By controlling the hydroxyl value to be low, the effect of maintaining good adhesion after the wet heat test can be obtained. It should be noted that commercially available products can be used for the multifunctional polyurethane acrylate.
[0144] In the present invention, the active energy ray curing resin contained in the active energy ray curing coating composition preferably includes a multifunctional (meth) acrylate compound and a multifunctional polyurethane acrylate. In this case, the multifunctional polyurethane acrylate more preferably includes 30 to 90 parts by mass, preferably 50 to 85 parts by mass, relative to 100 parts by mass of the resin component contained in the active energy ray curing coating composition. When the amount of the multifunctional polyurethane acrylate is less than 30 parts by mass, the adhesion is reduced, and when the amount of the multifunctional polyurethane acrylate exceeds 90 parts, the hardness of the coating layer may be damaged.
[0145] There is no particular limitation on the synthesis method of the polyfunctional urethane (meth)acrylate, and the polyfunctional urethane (meth)acrylate can be obtained, for example, by a urethanization reaction of a polyisocyanate compound and a hydroxyl-containing (meth)acrylate. The above reaction is preferred because it is suitable for obtaining a polyfunctional urethane (meth)acrylate having three or more acryloyl groups in one molecule.
[0146] In addition, for the purpose of adjusting the molecular weight and molecular flexibility of the multifunctional polyurethane (meth)acrylate, before reacting the polyisocyanate with the hydroxyl-containing (meth)acrylate, a chain-extended polyurethane prepolymer having a terminal isocyanate group may be produced by reacting a known general-purpose polyol with the polyisocyanate, and the chain-extended polyurethane prepolymer may be reacted with the hydroxyl-containing (meth)acrylate to use the obtained product as component (A). The above-mentioned polyol is not particularly limited, and examples thereof include ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, neopentyl glycol, 1,4-butanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol and other ethylene oxide / propylene oxide adducts, polyester polyols, and ethylene oxide / propylene oxide copolymers.
[0147] The active energy ray-curable coating composition may include, for example, a hydroxyl-containing (meth)acrylate. As the hydroxyl-containing (meth)acrylate, for example, 2-hydroxyethyl acrylate or 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate or 2-hydroxypropyl methacrylate, ethylene glycol mono(meth)acrylate, propylene glycol mono(meth)acrylate, 2-hydroxy-3-methoxypropyl acrylate or 2-hydroxy-3-methoxypropyl methacrylate, pentaerythritol triacrylate or pentaerythritol trimethacrylate, N-hydroxymethyl acrylamide or N-hydroxymethyl methacrylamide, N-hydroxy acrylamide or N-hydroxymethyl methacrylamide, etc., may be cited. Their lactone adducts [such as PCL-FA or PCL-FM series manufactured by Daicel Corporation, etc.] may also be used.
[0148] Examples of commercially available products in the form of hydroxyl-containing (meth)acrylates include DPHA (manufactured by DaicelCytec), PETRA (manufactured by DaicelCytec: pentaerythritol triacrylate), PETIA (manufactured by DaicelCytec), Aronix M-403 (manufactured by Toagosei Co., Ltd.: dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate), Aronix M-402 (manufactured by Toagosei Co., Ltd.: dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate), Aronix M-400 (manufactured by Toagosei Co., Ltd.: dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate), SR-399 (manufactured by Sartomer: dipentaerythritol hydroxypentaacrylate), KAYARAD DPHA (manufactured by Nippon Kayaku Co., Ltd.), and KAYARAD DPHA-2C (manufactured by Nippon Kayaku Co., Ltd.). Some of the above products have compounds containing hydroxyl groups.
[0149] In addition, as commercially available products of multifunctional polyurethane (meth)acrylates having three or more (meth)acryloyl groups in one molecule, specific product names may be cited, for example, bifunctional polyurethane (meth)acrylates ("UX-2201" or "UX-8101" manufactured by Nippon Kayaku Co., Ltd., "UF-8001", "UF-8003", "UX-6101", "UX-8101" manufactured by Kyoeisha Chemical Co., Ltd., "Ebecryl 244", "Ebecryl 284", "Ebecryl 2002", "Ebecryl 4835", "Ebecryl 4883", "Ebecryl 8807", "Ebecryl 6700" manufactured by Daicel Cytec Co., Ltd.), trifunctional polyurethane (meth)acrylates ("Ebecryl 254", "Ebecryl 264", "Ebecryl 265" manufactured by Daicel Cytec Co., Ltd.), tetrafunctional polyurethane (meth)acrylates ("Ebecryl 254", "Ebecryl 264", "Ebecryl 265" manufactured by Daicel Cytec Co., Ltd.), Cytec), 6-functional urethane (meth) acrylate ("Ebecryl1290k", "Ebecryl5129", "Ebecryl220", "KRM8200", "Ebecryl1290N" manufactured by Daicel Cytec), 9-functional urethane (meth) acrylate ("KRM7804" manufactured by Daicel Cytec), 10-functional urethane (meth) acrylate ("KRM8452", "KRM8509" manufactured by Daicel Cytec), 15-functional urethane (meth) acrylate ("KRM8655" manufactured by Daicel Cytec), etc.
[0150] For example, commercially available products such as Aronix M-400, M-450, M-305, M-309, M-310, M-315, M-320, TO-1200, TO-1231, TO-595, TO-756 (all manufactured by Toagosei Co., Ltd.), KAYARD D-310, D-330, DPHA, DPHA-2C (all manufactured by Nippon Kayaku Co., Ltd.), and NIKALAC MX-302 (manufactured by Sanwa Chemical Co., Ltd.) which are polyfunctional (meth)acrylate compounds containing at least two (meth)acryloyl groups in the molecule can also be used.
[0151] By using a radiation-curable resin containing the above-mentioned multifunctional (meth)acrylate compound, multifunctional urethane acrylate, etc., there is an advantage that a molded decorative laminate film having excellent light resistance and no light degradation due to long-term use can be obtained.
[0152] (Photopolymerization Initiator)
[0153] The active energy ray-curable coating composition of the present invention preferably contains a photopolymerization initiator. Due to the presence of the photopolymerization initiator, the resin component is well polymerized by irradiation with active energy rays such as ultraviolet rays. Examples of the photopolymerization initiator include alkylphenone-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, titanocene-based photopolymerization initiators, and oxime ester-based polymerization initiators. Examples of the alkylphenone-based photopolymerization initiator include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone. Examples of the acylphosphine oxide-based photopolymerization initiator include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. Examples of the titanocene-based photopolymerization initiator include bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium. Examples of the oxime ester-based polymerization initiator include 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(0-acetoxime), oxyphenylacetic acid, 2-[2-oxo-2-phenylacetoxyethoxy]ethyl ester, and 2-(2-hydroxyethoxy)ethyl ester. These photopolymerization initiators may be used alone or in combination of two or more.
[0154] Among the above-mentioned photopolymerization initiators, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 and 2,2-dimethoxy-1,2-diphenylethane-1-one are more preferably used.
[0155] The preferred amount of the photopolymerization initiator is 0.01 to 20 parts by mass, more preferably 1 to 10 parts by mass, based on 100 parts by mass of the resin component of the active energy ray-curable coating composition.
[0156] (Other ingredients)
[0157] The active energy ray-curable coating composition may contain compounds that are usually added as coating materials as other components. Other components include ultraviolet light absorbers (UVA), light stabilizers (HALS), binder resins or crosslinking agents, pigments, surface conditioners, defoamers, conductive fillers, solvents, etc.
[0158] In addition, for the mixing or viscosity adjustment of each component contained in the active energy ray curable coating composition, a solvent can also be used. As the solvent, for example, esters, ethers, alcohols, amides, ketones, aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, etc., which are currently known organic solvents for coatings, can be used in one or in combination of two or more. It should be noted that, when using the above-mentioned solvents, if there are volatile substances remaining in the laminated film, the volatile substances volatilize when the substrate is decorated, and sometimes pinholes and expansions may occur. Therefore, it is preferred to fully reduce the volatile substances contained in the laminated film.
[0159] In addition, the active energy ray-curable coating composition preferably further contains 0.5 to 60 parts by weight of an inorganic / organic filler having an average primary particle size of 100 nm or less. Thus, anti-blocking properties, high scratch resistance, and surface hardness can be improved. The lower limit of the above-mentioned compounding amount is more preferably 1% by weight, and the upper limit is more preferably 50% by weight.
[0160] As the above-mentioned inorganic filler, there can be mentioned silicon dioxide, fine powder glass, aluminum oxide, calcium carbonate, kaolin, clay, sepiolite (magnesium silicate), talc (magnesium silicate), mica (aluminum silicate), xonotlite (calcium silicate), aluminum borate, hydrotalcite, wollastonite (calcium silicate), potassium titanate, titanium oxide, barium sulfate, magnesium sulfate, magnesium hydroxide, yttrium oxide, cerium oxide, silicon carbide, boron carbide, zirconium oxide, aluminum nitride, silicon nitride, or their eutectic mixtures, or non-metallic inorganic materials so-called ceramic fillers obtained by molding, firing, etc. Among them, silicon dioxide, aluminum oxide, zirconium oxide or their eutectic mixtures are preferred from the aspects of price and effect.
[0161] Examples of the organic filler include beads of acrylic, styrene, silicone, polyurethane, acrylic polyurethane, benzoguanamine, and polyethylene resins.
[0162] In addition, as commercially available products, organic silica sols such as MIBK-ST, MEK-ST-UP, MEK-ST-L, MEK-AC-2140Z (produced by Nissan Chemical Industries, Ltd.), SIRMIBK15ET%-H24, SIRMIBK15ET%-H83, and ALMIBK30WT%-H06 (produced by CIK nanotek) can be used.
[0163] The active energy ray-curable coating composition may contain 0.5% to 20% by weight (solid content ratio in the coating) of a polyisocyanate compound having an isocyanate group. It is preferred to mix the polyisocyanate compound from the perspective of being able to impart formability (stretchability) and scratch resistance. The lower limit of the above-mentioned mixing amount is more preferably 2% by weight, and the upper limit is more preferably 18% by weight.
[0164] The thickness of the hard coating layer (B) is not particularly limited, but is preferably 5 μm to 100 μm, more preferably 7 μm to 70 μm, and even more preferably 10 μm to 50 μm, in order to maintain performance such as surface hardness and scratch resistance.
[0165] The coating viscosity also depends on the method of forming the coating film, and is preferably 50 mPa·s to 5000 mPa·s, and more preferably 100 mPa·s to 3000 mPa·s. If the viscosity is lower than this value, it is difficult to ensure the film thickness, and the workability is deteriorated. If the viscosity is higher than this value, air remains, so that the problem of expansion occurs during molding.
[0166] (Printing layer (D))
[0167] The decorative laminated film for solar cell assembly of the present invention may have a printed layer formed by printing. By providing such a layer, it is preferred from the aspect of obtaining a specific appearance brought by the printed layer. The printing method is not particularly limited, and it can be formed by known methods such as inkjet printing, screen printing, offset printing or flexographic printing. In particular, by using inkjet printing, various printed layers can be formed at low cost, which is preferred from this aspect. In addition, when printing, printing using active energy ray-curable ink can also be performed.
[0168] The curing component contained in the printed layer is not particularly limited, and for example, the polyols and polyurethane resins listed in the decorative layer (C) can be used.
[0169] The above-mentioned printing layer preferably contains a bright pigment as a pigment of the ink. As the above-mentioned bright pigment, for example, the bright pigment listed in the decorative layer (C) can be used. By including the above-mentioned bright pigment, a more specific appearance can be obtained, so it is preferred. The mixing amount of the above-mentioned bright pigment is preferably 0.1% by mass to 60% by mass relative to the total solid content of the printing layer. By using the above-mentioned mixing amount, a printing layer with both design and light transmittance can be formed, which is preferred from this aspect. The above-mentioned mixing amount is more preferably 1% by mass to 50% by mass, and further preferably 5% by mass to 30% by mass.
[0170] The printed layer may further contain other pigments that are not bright pigments. By containing other pigments, the design can be further improved. As other pigments, for example, the pigments listed in the decorative layer (C) can be used. It should be noted that when using such other pigments that are not bright pigments, the total light transmittance Tt of the decorative laminate film for solar cell modules is also preferably 50% or more and 90% or less.
[0171] (Transparent filler layer (H))
[0172] In the decorative laminate film for a solar cell module of the present invention, particularly when a printed layer is provided between a support layer and an adhesive layer, it is preferred that a transparent filler layer be formed adjacent to the printed layer.
[0173] That is, it is a layer used to fill the unevenness generated by printing to make it smooth and ensure the closeness and smoothness of the adjacent adhesive layer. When the adhesive layer is provided on the unevenness of the printed layer, the uneven shape of the printed layer sometimes impairs the smoothness of the adhesive layer, causing a reduction in the contact area when bonding to the coated object, resulting in poor bonding. The main agent contained in the above-mentioned transparent filler layer is not particularly limited, and for example, the polyols listed in the above-mentioned decorative layer (C) can be used.
[0174] (Adhesive layer (F))
[0175] The decorative laminated film for solar cell module of the present invention has an adhesive layer. The adhesive layer is used to make the laminated film adhere to the surface of the substrate when the laminated film is used to decorate the substrate. The adhesive layer of the conventional decorative laminated film is used for the purpose of permanent bonding between the substrate and the laminated film. On the other hand, the decorative laminated film for solar cell module of the present invention is a peelable laminated film, so the adhesive layer preferably has a moderate adhesive force.
[0176] The appropriate adhesive strength of the adhesive layer can be expressed as a range of 1 N / 25 mm to 50 N / 25 mm when the decorative laminate film (L) is peeled from the solar cell module after the protective film (A) is peeled off from the decorative laminate film for solar cell module.
[0177] If the adhesive force exceeds 50N / 25mm, it has the same adhesive force as a general adhesive layer, so it is completely close to the adherend and it becomes difficult to peel it off. On the other hand, if the adhesive force is less than 1N / 25mm, the adhesive force is insufficient and it is easy to cause warping. By making the adhesive force within such a range, there is no problem in construction and the pasting workability can be easily performed.
[0178] The above-mentioned adhesive strength is a value measured under the conditions described in Examples using CARBOGLASS polish (transparent (t=2.00 mm) manufactured by AGC Corporation.
[0179] The dry film thickness of the adhesive layer is preferably 1 μm to 50 μm. In order to obtain appropriate adhesion, it is not preferable to have a film thickness that is too thick or too thin. The lower limit is more preferably 3 μm, and more preferably 5 μm. The upper limit is more preferably 40 μm, and more preferably 30 μm.
[0180] In one embodiment, the adhesive layer has a release film on the surface opposite to the resin substrate, and the surface roughness of the release film on the adhesive layer side is 20 nm to 100 nm.
[0181] The adhesive contained in the adhesive layer is not particularly limited as long as it is a conventionally known adhesive, and examples thereof include VYLON UR-3200 (manufactured by Toyobo Co., Ltd.), UR-1361ET (manufactured by Toagosei Co., Ltd.), and SK Dyne 1811L (manufactured by Soken Chemical Co., Ltd.).
[0182] The adhesive may be formed by applying the adhesive and drying it, or by laminating adhesive sheets. The adhesive layer may be made of various known materials, and as the resin, acrylic resin, polyurethane resin, polyester resin, silicone resin, etc. are preferred, and isocyanate is preferably used for crosslinking.
[0183] In the decorative laminate film for solar cell modules of the present invention, the refractive index Fa of the adhesive layer is 1.3 to 1.8, preferably 1.4 to 1.6. In addition, the difference |Fa-Fg| between the refractive index Fg of the surface of the solar cell module to be coated and the adhesive layer is preferably 0 to 0.5, more preferably 0 to 0.1.
[0184] The refractive index Fa of the adhesive layer is a value obtained by preparing a film consisting only of the adhesive layer and measuring it. The refractive index Fg of the surface of the solar cell module is a value determined by the material of the substrate used and is a value measured at d-ray wavelength and room temperature (23°C).
[0185] The above Fa can be adjusted to fall within the above range by appropriately changing the thickness of the adhesive layer, the composition of the adhesive layer, and the like.
[0186] In addition, in this invention, the refractive index is measured by the method based on JIS K0062 using an Abbe refractometer.
[0187] In order to adjust the refractive index to the above range, the adhesive layer may contain low-refractive-index particles or high-refractive-index particles.
[0188] (Low refractive index particles)
[0189] As the low refractive index particles, for example, hollow silica fine particles can be mentioned. As the hollow silica fine particles, for example, Thrulya 4320 (manufactured by JGC Catalysts & Chemicals Co., Ltd.) can be mentioned. As the low refractive index particles, hollow acrylic fine particles can be used.
[0190] The content of the hollow silica particles is preferably 5 parts by mass or more and 90 parts by mass, more preferably 10 parts by mass to 70 parts by mass, and even more preferably 15 parts by mass to 50 parts by mass, based on 100 parts by mass of the solid content of the adhesive layer.
[0191] (High refractive index particles)
[0192] Examples of high refractive index particles include zirconium oxide particles. Examples of zirconium oxide particles include NANON ZR-010 (manufactured by SOLAR CO., LTD.). Examples of high refractive index particles include titanium dioxide particles.
[0193] The content of the high refractive index particles is, for example, 5 parts by mass or more and 90 parts by mass or less, more preferably 10 parts by mass to 70 parts by mass, and further preferably 15 parts by mass to 50 parts by mass, based on 100 parts by mass of the solid content of the adhesive layer.
[0194] (Supporting layer (G))
[0195] The decorative laminated film for solar cell module of the present invention has a support layer (G). As described above, since the support layer (G) is provided, the strength of the laminated film is maintained and it can be peeled off without breaking after being attached to the solar cell module. In addition, the workability when pasting the decorative laminated film is also improved. For example, it is also possible to stretch the soft film while applying force and paste it by manual operation.
[0196] The thickness of the support layer may be adjusted appropriately, and is preferably 25 μm to 200 μm, for example.
[0197] The support layer (G) may contain the other components. For example, when an ultraviolet light absorber (UVA) is included, weather resistance can be improved, so it is preferred. As the ultraviolet light absorber, a benzotriazole-based ultraviolet light absorber with a molecular weight of 400 or more or a triazine-based ultraviolet light absorber with a molecular weight of 400 or more is preferred. As a specific example of the former, Tinuvin 234 of BASF Japan Co., Ltd. and ADK STAB LA-31RG of ADEKA Co., Ltd. can be cited, and as a specific example of the latter, Tinuvin 1577 of BASF Japan Co., Ltd. can be cited.
[0198] As the supporting layer (G), conventionally known films such as thermoplastic polyurethane (TPU), biaxially oriented polyester film, biaxially oriented polypropylene film, soft vinyl chloride film, unoriented polypropylene film, unoriented polyester film, polycarbonate film, acrylic resin film, and fluorine film can be used. Among them, thermoplastic polyurethane (TPU) and soft vinyl chloride film are preferred because they have high followability, flexibility, stretchability, etc. and can be applied to curved surfaces other than flat surfaces.
[0199] The decorative laminate film for a solar cell module of the present invention preferably has a surface free energy γac of the decorative laminate film (L) in a state where the protective film is peeled off and a surface free energy γap of the peeled side of the protective film satisfying the following formula (2).
[0200] 50.0≤(γac / γap)×100≤110.0 (2)
[0201] The lower limit of the above formula (2) is more preferably 70.0, and even more preferably 90.0. The upper limit is more preferably 105.0, and even more preferably 100.0.
[0202] The surface free energy is a value calculated from the Owens and Wendt formula by finding the contact angle between water and diiodomethane on the coating surface.
[0203] In the decorative laminated film for a solar cell module of the present invention, it is preferred that the Martens hardness HM(L) of the decorative laminated film (L) after peeling off the protective film satisfies the following formula (3).
[0204] 2.0N / mm 2 ≤HM(L)≤50.0N / mm 2 (3)
[0205] The Martens hardness HM (L) can be measured using a micro-hardness tester (model HM2000) manufactured by Fischer Instruments Co., Ltd. The micro-hardness tester provides data of Martens hardness calculated from a graph of indentation depth and load.
[0206] The lower limit of the above formula (3) is more preferably 5.0 N / mm 2 , more preferably 10.0N / mm 2 .
[0207] In addition, the upper limit is more preferably 30.0 N / mm 2 , more preferably 20.0N / mm 2 .
[0208] When the protective film of the decorative laminate film for solar cell modules is peeled off at a speed of 5.0 mm / sec, the surface roughness Ra of the decorative laminate film (L) is formed, which becomes an evaluation scale that needs to be maintained. When it is outside the range of formulas 1 and 2, the surface roughness of the laminate film cannot be formed appropriately, and the design and light transmittance are reduced. In addition, when it is outside the range of formula 3, the surface gloss after the test is reduced in terms of reliability such as heat resistance test.
[0209] (Method for producing decorative laminated film)
[0210] Regarding the layers other than the protective film (A) and the supporting layer (G) constituting the decorative laminated film for solar cell modules of the present invention, a coating composition is prepared by dissolving the components constituting each layer in a solvent, and the coating composition is applied to the supporting layer (G) and dried, and the protective film (A) is laminated on the laminated body thus formed, thereby obtaining a laminated structure. Then, the decorative laminated film for solar cell modules of the present invention can be obtained by thermal curing or energy ray curing.
[0211] In the above-mentioned decorative laminated film for solar cell modules, it is important that the decorative layer (C) has a high light transmittance. In order to form such a decorative layer (C), it is preferred to apply the above-mentioned coloring paint by applying a shear force to form the decorative layer (C). "Applying a shear force for coating" means that the paint is passed through the gap at a certain speed together with the film passing through the gap, thereby applying shear to the paint, and the flaky bright pigment contained in the paint is rearranged and oriented better.
[0212] The coating method for forming the above-mentioned layers is not particularly limited, and coating can be performed using, for example, a coater, a die coater, a rod coater, a roll coater, a comma coater, etc. After the coating solution is applied by the above-mentioned coating method, it can be heated and dried to remove the solvent in the coating solution.
[0213] The heating and / or active energy ray irradiation for curing the above-mentioned layers may be performed sequentially on each layer after the layers are formed, or may be performed after the entire laminated structure is formed. Either method may be used.
[0214] As described above, the adhesive layer (F) may be bonded by lamination rather than coating and drying. That is, it may be formed by preparing a film composed of the adhesive layer (F) and bonding it to a film by lamination.
[0215] (How to use decorative laminate film)
[0216] The decorative film for a solar cell module of the present invention can be used by being attached to a solar cell module. In this case, the protective film (A) is peeled off before use.
[0217] The decorative laminate film for solar cell module of the present invention can be attached to the light-receiving surface or the back surface of the solar cell module. When attached to the back surface, the decorative layer (C) is preferably the same color as the cell from the viewpoint of good design.
[0218] There is no particular limitation on the solar cell unit to which the decorative laminate film for the solar cell module of the present invention can be applied. For example, the photoelectric conversion layer can use polycrystalline silicon units, single crystal silicon units, amorphous silicon units, microcrystalline silicon units, compound solar cell units such as CIGS, organic thin film solar cell units, dye-sensitized solar cell units and the like.
[0219] The decorative film for solar cell module of the present invention can be attached to a glass substrate or a polycarbonate substrate. The glass substrate has a flat plate shape. When the decorative film for solar cell module of the present invention is attached thereto, it can be done by manual work or thermal lamination. In addition, energy ray curing can be performed during the manufacture of the decorative laminated film, or active energy ray curing can be performed after attachment.
[0220] The polycarbonate substrate has a flat plate, a curved shape, a three-dimensional shape, etc. Among these, when pasting on a flat plate-shaped substrate, the same method as the above-mentioned glass substrate can be used.
[0221] When the solar cell module decorative film of the present invention is attached to a curved or three-dimensional polycarbonate substrate, the solar cell module decorative film needs to be attached while deforming the solar cell module decorative film. Therefore, it is preferred to make the solar cell module decorative film have a certain degree of stretchability.
[0222] Specifically, for example, biaxially oriented polyester films and biaxially oriented polypropylene films that can be easily applied to flat substrates are preferably not used as the support layer (G) for substrates that need to be attached while deforming, and thermoplastic polyurethane (TPU) is preferably used.
[0223] As a method for attaching the decorative film for solar cell modules to a curved surface, a method using a machine such as vacuum forming can be cited, but a method based on manual work can also be cited. For example, the following method can be cited: after attaching a part of the decorative film to the substrate, the decorative film is stretched with one hand, and the substrate and the film are closely attached to each other along the height difference and three-dimensional curved surface using a scraper held by the opposite hand.
[0224] In addition, for a three-dimensional substrate that needs to be deformed while being pasted, curing with active energy rays is preferably performed after pasting to the substrate, rather than when the decorative laminate film is produced. For example, it is preferred that the above-mentioned layers are coated on the protective film (A) and dried, and then the adhesive layer (F) is crimped to the substrate having a three-dimensional shape for decoration, and then irradiated with active energy rays. With such a method, after the uncured decorative laminate film is deformed into the shape of the substrate, the resin can be completely cured by energy ray irradiation, and it can be easily deformed into the shape of the substrate.
[0225] Example
[0226] Hereinafter, the present invention will be described by way of Examples. In the Examples, unless otherwise specified, % in the blending ratio means % by weight. The present invention is not limited to the Examples shown below.
[0227] The composition of each layer is shown in Tables 1 to 3.
[0228] [Table 1]
[0229]
[0230] Main agent: "COATAX A-200" manufactured by Toray Fine Chemicals Co., Ltd., polyacrylic acid polyol resin
[0231] Curing agent: "H2550" manufactured by NIPPON PAINT AUTOMOTIVE COATINGS CO., LTD., isocyanate compound
[0232] Pigment: "Xirallic (registered trademark) T60-23 SW Galaxy Blue" manufactured by MERCK
[0233] Pigment: ALPASTE 93-0467, a product of Toyo Aluminium Co., Ltd.
[0234] Pigment: Cyanine Blue G314 manufactured by Sanyo Pigment Co., Ltd.
[0235] [Table 2]
[0236]
[0237] Mitsubishi Rayon Co., Ltd., trade name "LR2731", acrylic polyol resin
[0238] Duranol T5650E, a product of Asahi Kasei Corporation, polycarbonate diol
[0239] KRM-8452: manufactured by Daicel-Allnex, multifunctional urethane acrylate oligomer, Mw 3,884, acrylic acid equivalent 120 g / eq
[0240] KRM-9322: Made by Daicel-Allnex, urethane acrylate
[0241] Curing agent: "H2550" manufactured by NIPPON PAINT AUTOMOTIVE COATINGS CO., LTD., isocyanate compound
[0242] Omnirad 127: Made by IGM RESINS, α-hydroxyacetophenone
[0243] UVA1: Benzotriazole compounds
[0244] UVA2: Triazine compounds
[0245] HALS: Hindered Amine Compounds
[0246] [Table 3]
[0247]
[0248] "SK Dyne 1811L" manufactured by Soken Chemical Co., Ltd.
[0249] Shin-Etsu Chemical Co., Ltd. Trade names "KR-3704, KR3700"
[0250] SOLAR CO., LTD., trade name "NANON ZR-010", zirconium oxide
[0251] "Thrulya 4320" manufactured by JGC Catalysts & Chemicals Co., Ltd.
[0252] "TD-75" manufactured by Soken Chemical Co., Ltd., xylylene diisocyanate trimethylolpropane adduct
[0253] <Production of Decorative Film>
[0254] (1) Formation of decorative layer
[0255] The coating solution was applied onto the support layer (base film) using a Baker-type coater so that the dry film thickness of the decorative layer would be a predetermined thickness, and dried at 100° C. for 5 minutes to obtain a decorative layer.
[0256] The support layer used was a thermoplastic polyurethane film "ESMER URSPX98" manufactured by Nihon Matai.
[0257] (2) Formation of two-component curing hard coating
[0258] In the same manner as above, a two-component curing coating solution was applied to the decorative layer prepared in (1) so that the dry film thickness of the hard coating layer became a predetermined thickness, and dried at 100° C. for 5 minutes. Then, a protective film and the hard coating layer were laminated using a laminator or the like, and cured at 50° C. for 7 days to obtain a hard coating layer.
[0259] (3) Formation of active energy ray-curable hard coat layer
[0260] Using a bar coater, an active energy ray curable coating solution was applied to the decorative layer prepared in (1) so that the dry film thickness of the hard coat layer became a predetermined thickness, and dried at 80°C for 1 minute. Then, a protective film and the hard coat layer were laminated using a laminator or the like, and irradiated with a cumulative light dose of 2000 mJ / cm 2 of active energy rays, thereby obtaining a hard coating.
[0261] (4) Formation of Adhesive Layer
[0262] On the substrate surface different from the surface on which the decorative layer and the hard coating layer are laminated, the coating solution is applied using a Baker-type coater so that the dry film thickness of the adhesive layer becomes 3 μm to 60 μm, and dried at 100° C. for 5 minutes to apply the adhesive layer. Then, a spacer and the adhesive layer are bonded together using a laminator or the like, and cured at 50° C. for 4 days to obtain a decorative film having an adhesive layer.
[0263] The protective films used were TORAYFAN#40-2500 (manufactured by Toray Industries, Inc.) and KB film N30 (manufactured by KIMOTO Corporation).
[0264] <Component Production>
[0265] The decorative laminate film produced by the above-mentioned manufacturing method was manually attached to a glass single crystal silicon cell using a squeegee at room temperature.
[0266] The following items were evaluated for the obtained decorative laminated film for solar cell modules.
[0267] (Total light transmittance Tt)
[0268] The total light transmittance was measured using a spectrophotometer U-4100 (Hitachi High-Technologies Corporation) in the wavelength range of 380.0 nm to 810.0 nm using an integrating sphere.
[0269] (Reflectivity R)
[0270] Using a U-3310 spectrophotometer (manufactured by Hitachi Ltd.), the wavelength scanning mode was used to measure the region from 380 nm to 1300 nm at a scanning speed of 300 nm / min and a sampling interval of 0.5 nm.
[0271] (Refractive index Fa, Fg)
[0272] The refractive index was measured using an Abbe refractometer manufactured by ATAGO Co., Ltd.
[0273] (Design (reflective color))
[0274] A decorative laminate film was attached to a black Gelpoly sheet, and the color tone was visually confirmed after the protective film was peeled off.
[0275] ○: The color tone can be visually identified
[0276] ×: The color tone cannot be visually identified (light color)
[0277] (Output)
[0278] Using a solar simulator (1kW / m 2 The solar cell module was irradiated with light (the spectral consistency was set to meet JIS C8912 A grade), and the output (W) was measured using an IV curve plotter MP-160 (manufactured by Eikon Seiki). The output ratio was evaluated as follows, with the ratio when there was no decorative layer being 100.
[0279] 〇:More than 50%
[0280] ×: Less than 50%
[0281] (Adhesion)
[0282] The decorative laminated film was cut into strips of 25 mm x 200 mm and attached to CARBOGLASS polish (transparent) (t = 2.0 mm) manufactured by AGC Corporation. After the protective film was peeled off, the peel strength of the decorative laminated film was measured when it was peeled off in a 180° direction at a speed of 200.0 mm / sec.
[0283] (Peelability)
[0284] In the evaluation of the adhesive force, whether or not the decorative laminated film can be peeled off without any problem was evaluated.
[0285] ○: Can be peeled off.
[0286] ×: The adhesive force is too high to be peeled off, or the adhesive force is too low to be peeled off easily.
[0287] (Ra(C) / Ra(P))
[0288] The value of [Ra(C) / Ra(P)]×100 was calculated from the surface roughness Ra(C) of the decorative laminate film from which the protective film was peeled off at a speed of 5.0 mm / sec and the surface roughness Ra(P) on the side from which the protective film was peeled off.
[0289] If it is less than 70, the protective film cannot be attached and it is difficult to give a shape.
[0290] When it exceeds 140, the protective film becomes difficult to peel off and the surface condition becomes poor.
[0291] (Concave-convex transfer property)
[0292] The outermost surface of the decorative laminated film from which the protective film was peeled, that is, the surface of the hard coating layer was visually observed.
[0293] ○: Good transferability
[0294] ×: Poor transfer
[0295] (Constructibility)
[0296] The sticking workability when the decorative laminate film was manually stuck to the single crystal silicon cell of glass was evaluated.
[0297] 0: No problems, construction can be carried out.
[0298] ×: The adhesive force is low and construction is impossible, or the adhesive force is high and position adjustment is difficult.
[0299] (Reliability (Moisture and Heat Resistance))
[0300] The decorative laminate film was cut into 50 mm×50 mm pieces, attached to a glass plate, and after peeling off the protective film, placed in an environment of 85°C and 85% humidity. After 1500 hours, the surface appearance of the hard coating layer as the outermost layer was visually observed.
[0301] ○: No adverse events
[0302] ×: There are defects in appearance such as cracks
[0303] (Weather resistance)
[0304] A 1200-hour accelerated weathering test was conducted using a sunlight weathering tester S80 (sunlight carbon arc accelerated weathering tester, manufactured by Suga Test Instruments) in accordance with JIS B 7753. The hard coating surface was irradiated with ultraviolet rays, and the color difference between the color tone before the test and the color tone 1200 hours after the start of the test was calculated by the following formula (4), and the evaluation was performed according to the following criteria.
[0305] Color difference = [(ΔL*)2+(Δa*)2+(Δb*)2]1 / 2(4)
[0306] The symbols in the formula have the following meanings.
[0307] ΔL* is the absolute value of the difference between the L* value before the test and the L* value after the test.
[0308] Δa* is the absolute value of the difference between the a* value before the test and the a* value after the test.
[0309] Δb* is the absolute value of the difference between the b* value before the test and the b* value after the test.
[0310] <Evaluation Criteria>
[0311] ○: The color difference calculated from the formula (1) is less than 3.0.
[0312] ×: The color difference calculated from the formula (1) is 3.0 or more.
[0313] (Protective film peelability)
[0314] After the protective film and the hard coat layer were bonded together, they were cured for 7 days in an environment of 50° C. to obtain a laminated film. The peelability of the protective film when it was peeled off by hand from the laminated film was evaluated.
[0315] ○: The coating film can be peeled off without being damaged.
[0316] ×: During peeling, the coating film suffered cohesive failure, or the protective film was not attached to the hard coating surface and peeled off naturally.
[0317] (Dry film thickness)
[0318] The thickness of the film obtained by applying the coating solution on the support layer and drying the film was measured using a constant pressure thickness meter manufactured by TECLOCK Corporation.
[0319] (Surface free energy γac and γap)
[0320] The decorative laminated film was cut into 50 mm×50 mm, and the contact angles of DIW (ion exchange water) and diiodomethane were measured using an automatic contact angle meter (Dmo-701 manufactured by Kyowa Interface Science Co., Ltd.) under the conditions of a droplet size of 1 μL and 1 second after the droplet was added, with respect to the protective film side of the decorative laminated film from which the protective film was peeled off at a speed of 5.0 mm / sec and the surface of the decorative laminated film side after the protective film was peeled off at a speed of 5.0 mm / sec, in an environment of 20°C to 23°C, and the surface free energy of each surface was calculated by the Owens and Wendt formula to obtain the surface free energy γac of the protective film side of the decorative laminated film from which the protective film was peeled off at a speed of 5.0 mm / sec. The surface free energy γap of the decorative laminated film from which the protective film was peeled off at a speed of 5.0 mm / sec was also obtained by the same procedure.
[0321] γac / γap×100 was calculated from the obtained values of each surface free energy.
[0322] (Martens hardness HM)
[0323] The test sample was cut into 50 mm × 50 mm pieces and attached to a glass plate. After peeling off the protective film, the Martens hardness HM (L) of the decorative laminate film was calculated from the indentation depth under the maximum load using a HM2000 micro hardness tester manufactured by Fischer under the conditions of a Vickers diamond indenter, a load speed of 5 mmN / 20 s, and a creep of 5 s.
[0324] [Table 4]
[0325]
[0326] [Table 5]
[0327]
[0328]
[0329] Industrial Applicability
[0330] The decorative laminate film for a solar cell module of the present invention can be used for decoration of solar cells.
[0331] Explanation of symbols
[0332] (A) Protective film
[0333] (B) Hard coating
[0334] (C) Decorative layer
[0335] (D) Printing layer
[0336] (F) Adhesive layer
[0337] (G) Support layer
[0338] (H) Transparent filler layer
Claims
1. A decorative laminate film for a solar cell module, comprising a protective film (A), a hard coating layer (B), a decorative layer (C), a support layer (G) and an adhesive layer (F), characterized in that: The decorative laminate film (L) in a state where the protective film (A) is peeled off from the decorative laminate film for a solar cell module has a total light transmittance Tt of 50% to 90% at a wavelength of 380 nm to 810 nm, and a reflectance R of 5% to 40% at a wavelength of 380 nm to 1300 nm. The adhesive layer has a refractive index Fa of 1.3 or more and 1.8 or less.
2. The decorative laminate film for a solar cell module according to claim 1, wherein: The difference |Fa-Fg| between the refractive index Fa of the adhesive layer and the refractive index Fg of the surface of the solar cell module is 0 or more and 0.5 or less. 3 . The decorative laminate film for a solar cell module according to claim 1 , which can be peeled off after being bonded to the solar cell module.
4. The decorative laminate film for a solar cell module according to claim 1 or 2, wherein: The adhesive strength between the decorative laminate film (L) and the solar cell module in a state where the protective film (A) is peeled off from the decorative laminate film for the solar cell module is 1 N / 25 mm or more and 50 N / 25 mm or less.
5. The decorative laminate film for a solar cell module according to claim 1 or 2, wherein: The hard coat layer is a layer formed of a thermosetting coating composition or an active energy ray-curable coating composition.
6. The decorative laminate film for a solar cell module according to claim 1 or 2, wherein: The surface roughness Ra (C) of the decorative laminate film (L) from which the protective film is peeled off at a speed of 5.0 mm / sec and the surface roughness Ra (P) of the peeled side of the protective film satisfy the following formula (1): 50.0≤[Ra(C) / Ra(P)]×100≤210.0 (1).
7. The decorative laminate film for a solar cell module according to claim 1 or 2, wherein: The surface free energy γac of the decorative laminate film (L) in a state where the protective film is peeled off and the surface free energy γap on the peeled side of the protective film satisfy the following formula (2): 50.0≤(γac / γap)×100≤110.0 (2).
8. The decorative laminate film for a solar cell module according to claim 1 or 2, wherein: The Martens hardness HM(L) of the decorative laminated film (L) in a state where the protective film is peeled off satisfies the following formula (3): 2.0N / mm 2 ≤HM(L)≤50.0N / mm 2 (3)。
Citation Information
Patent Citations
Coating for lower layer formation used as groundwork of hard coat layer, and laminate formed by applying the coating for lower layer formation
JP2013119553A
Decorated solar cell module
JP2021027266A
Decorative film for solar cell module
JP2021027364A